Causative factors of low scores in the cambridge sample toefl test administered to students enrolled in the subjects Teaching Practice I and II in the Foreign Languages Department of the University of el Salvador during the years 2014-2016 - Galdámez Sigüenza, Altagracia Guadalupe
For many years, the University of El Salvador has been recognized for being dedicated to excellence in teaching and for preparing students in many disciplines who make a difference within the country. As well, the University provides well-prepared graduates with a great sense of humanism and a high quality of knowledge that brings to our society countless opportunities of growth and development in several areas. The Bachelor of Arts in English with Emphasis in Teaching option is considered one of the majors with the highest degree of demand in the campus, and since students get prepared to become English teaching professionals, they must take the authentic TOEFL test after graduating to be recognized as certified teachers by the Ministry of Education. However, before students get graduated they need to take their Teaching Practice subjects I and II in the fourth year of the major. By that time, they should have approved the five intensive English courses in which they are expected to reach an advanced English level. Thus, for students to take the Teaching Practice I subject and to be placed knowledgeably to develop their practicum, they are required to take the Cambridge Sample TOEFL Test which is a practice test for the certified and authentic TOEFL. Moreover, there have been researches regarding to students’ level of proficiency in the Foreign Languages Department (hereinafter referred to as “FLD”), and it was discovered that students are not entirely in the level of proficiency they are supposed to be, even after taking the Teaching Practice subjects. This research paper is a follow up to those investigations but in this case, the level of proficiency is not the only reason students are getting low scores. In the last years, students have been getting scores that do not reflect the English proficiency level they are supposed to have at that point of the major, and it is so alarming since most of them are not even reaching the minimum score required -which is going to be explained as well within this work. So, the current research presents the factors why students from the Bachelor of Arts in English with emphasis in Teaching option have been getting low scores during the years 2014-2016.